الوصية للوارث: دراسة فقهية تحليلية = The will for heirs: a juristic analytical study - Karim, Fatimah; Awang, Abdul Bari; Zakaria, Mohamad Sabri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
This research aims to study the topic of “The Will for Heirs: A Juristic Analytical Study.” It deals with the definitions of will or testament and heirs from the perspective of Islamic jurisprudence. It discusses the views of jurists regarding the ruling of will for heirs by discussing proofs of jurists on this issue in the light of Islamic law of inheritance. This research discovers that the Muslim jurists differed on the law of will for heirs according to three schools of thought: according to Shī’ah Imāmiyyah and some supporters of Zaydiyyah, the will for heirs is permissible in one-third whether approved by the other heirs or not. This view differs from the majority of jurists who invalidate the will for heirs except by the permission of the other heirs because their permission is like a forfeiture of their right. Others, such as Ẓāhiriyyah, opposed the implementation of will for heirs. They argued that the will, will cause dissatisfaction in other heirs or inheritors. On the other hand, the will for heirs is useful and beneficial for some of the needy heirs. The researchers rely on the inductive and analytical methods. One of the important findings of this research is that, relying on the majority opinion of jurists, the law of will for heirs is valid only with the permission of the rest of the heirs after the death of the testator; this is the best opinion based on the strength of the evidence and their keenness on the unity of the heirs of the deceased.